When the civic-participation play a crucial role on urban sustainability. The case study of the University of Rome “Tor Vergata” and the project “A playground for Aurora” - Fiorani, Gloria; Litardi, Irene (European Journal of Islamic Finance, 2020)
The sustainability has become a priority and playing an important role in the strategic choices of all actors, which look for economical, social and environmental sustainability to preserve “well-being” for future generations. The research focus is on the new role of University as a driver for sustainable development trough social responsibility in urban scenario. The research goals are: to develop a conceptual framework on the role of education at University level in promoting sustainability, according to the Third Mission approach, and to define the role of high Education in Urban Sustainability. The research is enriched by a case study called “A Playground for Aurora”, where the Department of Management and Law of the University of Rome “Tor Vergata” and the Government and Civil Society Research Group (GCS) played a crucial role to built and to regenerate an inclusive playground (with games accessible to disabled children). The case study is a specific example of student engagement, the importance of partnership, co-design and civic-crowdfunding with a view of Sustainable Developments Goals.